2009
DOI: 10.1590/s1517-86922009000500014
|View full text |Cite
|
Sign up to set email alerts
|

Força muscular versus pressão arterial de repouso: uma revisão baseada no treinamento com pesos

Abstract: RESUMoIntrodução: O exercício com pesos é atualmente recomendado para diferentes grupos de indivíduos. Seu principal objetivo é o aumento na força muscular, mas podem ocorrer outros resultados, como a redução na pressão arterial (PA) de repouso. Contudo, é pouco abordada a relação entre prescrição do treinamento com pesos, aumento da força e comportamento da PA de repouso em humanos. Objetivo: Analisar a PA após uma sessão aguda de exercícios com pesos e após um período de treinamento com pesos, em indivíduos … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2013
2013
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 44 publications
(112 reference statements)
0
2
0
1
Order By: Relevance
“…In fact, reduction of 40% in the risk of cerebrovascular accidents and of 15% in the risk of acute myocardial infarction has been reported after persistent reduction of 5 mmHg in rest SBP 29 . Polito 15 has highlighted that although RT may present important effects on the cardiovascular system, the main applicability of this kind of training is the alteration in the different expressions of muscle strength. Therefore, increase in muscle strength may provide reduction in muscular activation and metabolic demand for the same absolute effort.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, reduction of 40% in the risk of cerebrovascular accidents and of 15% in the risk of acute myocardial infarction has been reported after persistent reduction of 5 mmHg in rest SBP 29 . Polito 15 has highlighted that although RT may present important effects on the cardiovascular system, the main applicability of this kind of training is the alteration in the different expressions of muscle strength. Therefore, increase in muscle strength may provide reduction in muscular activation and metabolic demand for the same absolute effort.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, different studies have shown isolated reduction in SBP 10 , DBP 11 or in both simultaneously 12 . The differences observed in the magnitude of BP alteration after RT may be related to the influence of the manipulation of the variables involved in the prescription of RT and the characteristics of the studied sample [13][14][15] . Therefore, many studies which investigated the chronic effect of RT in rest BP in elderly subjects had different RT methods and individuals of both genders in their samples.…”
Section: Introductionmentioning
confidence: 99%
“…Segundo Polito,14 a magnitude e a duração de redução da PA após o treinamento resistido podem sofrer influência das próprias variáveis desse tipo de treinamento, como carga utilizada, número de repetições, número de séries, intervalo de repouso entre as séries, entre outras. Tais variáveis, quando manipuladas adequadamente, permitiriam atingir objetivos específicos,15 como a redução da PA de repouso.…”
unclassified